John 'Sandy' Atkinson interviewed by Rob Willis in the Rob and Olya Willis folklore collection. - Atkinson, John, 1932-; Willis, Rob, 1944-; Willis Olya (2015)
Folkloric recording.
Recorded with Olya Willis.
Accompanying material: 4 portraits of John Atkinson by Olya Willis.
Recorded on 13 May 2015 in Tatura, Victoria.
Timed summary available.
Keywords: Atkinson, John, -- 1932- -- Interviews; Cummeragunja Mission (N.S.W.) -- History; Yorta Yorta (Australian people) -- Interviews; Arts administrators -- Victoria -- Interviews; Arts administrators; Aboriginal community leaders